Resonant Frequencies of Small Arterial Segments as Determining Factors For Estimation of Terminal Segments in Electromechanical Arterial Tree Model - Stefan Borik; Ivo Cap; Branko Babusiak (Communications - Scientific letters of the University of Zilina, 2015)
A model of the nonsymmetrical arterial tree was analyzed. The arterial branching model was based on the principle of the electromechanical analogy. The nonsymmetrical arterial tree was divided to 7 arterial generations, starting from larger arteries towards small arteries and arterioles. For each generation the resonant frequency and the transfer function were calculated and there are presented the pressure simulation results for each arterial generation. Terminal segments were determined regarding to calculation of the resonant frequencies and the transfer functions and simulation results.